Considering visual-manual tasks performed during highway driving in the context of two different sets of guidelines for embedded in-vehicle electronic systems. (May 2017) - Kidd, David G.; Dobres, Jonathan; Reagan, Ian; Mehler, Bruce; Reimer, Bryan
Highlights: Visual demand of 4 tasks performed using two embedded in-vehicle systems was assessed. Pass/fail conclusions after applying the NHTSA and Alliance guidelines were compared. Pass/fail conclusions for 3 of the 4 tasks were the same for both guidelines. Relying on data from a single trial per NHTSA guidelines may reduce repeatability. Analysis of naturalistic driving data could help refine the visual demand thresholds. Abstract: The Alliance of Automobile Manufacturers and the National Highway Traffic Safety Administration have each developed a set of guidelines intended to help developers of embedded in-vehicle systems minimize the visual demand placed on a driver interacting with the visual-manual interface of the system. Though based on similar precepts, the guidelines differ in the evaluation methodologies and the criteria used to define safe levels of visual demand. The current study compared the pass/fail conclusions from applying the two guidelines. Four visual-manual tasks were evaluated using two embedded in-vehicle systems (Volvo Sensus, Chevrolet MyLink) during highway driving. Only a preset radio tuning task met the threshold for acceptable visual demand in both guidelines. The pass/fail conclusions for three of the four tasks [manual radio tuning (fail), preset radio tuning (pass), easy contact calling (fail)] performed using either system were the same for both guidelines; calling a contact with multiple possible numbers using MyLink failed both guidelines, and with Sensus the task passed the Alliance guidelines but not NHTSA's. Exploratory analyses suggested that broadening the age range of the participant sample specified in the Alliance guidelines beyond 45–65 year olds did not change pass/fail conclusions. Results from a Monte Carlo simulation suggested that relying on data from a single trial per the NHTSA guidelines may reduce the repeatability of pass/fail conclusions. Interestingly, the manual radio tuning task failed to pass both sets of guidelines, even though the organizations used it as a reference task for setting acceptable levels of visual demand. Perhaps this indicates that radios have become more difficult to tune than the ones that provided the basis for the guidelines; however, naturalistic driving studies have not indicated increased risk from tuning more modern radios. Analysis of glance behavior during naturalistic driving may provide opportunities to further refine the acceptable thresholds for visual demand.